Preceptor Development: Incorporating the Future of Nursing Recommendations and the American Nurses Credentialing Center Outcome-Based Continuing Education Model. Issue 3 (May 2023) - Schweitzer, Kelli; Graebe, Jennifer
Abstract : The American Nurses Credentialing Center outcome-based continuing education model is a method of outcomes-driven professional development that is learner-driven. This model can be used to incorporate the Future of Nursing recommendations into a preceptor development program. The use of this competency-driven model can empower preceptors and nursing professional development practitioners as they work together to facilitate the acquisition of preceptor competencies though learning experiences and achievement of outcomes.